Lactate production without hypoxia in skeletal muscle during electrical cycling: Crossover study of femoral venous-arterial differences in healthy volunteers - Gojda, Jan; Waldauf, Petr; Hrušková, Natália; Blahutová, Barbora; Krajčová, Adéla; Urban, Tomáš; Tůma, Petr; Řasová, Kamila; Duška, František (PloS one, 2019)
BACKGROUND: Aim of the study was to compare metabolic response of leg skeletal muscle during functional electrical stimulation-driven unloaded cycling (FES) to that seen during volitional supine cycling. METHODS: Fourteen healthy volunteers were exposed in random order to supine cycling, either volitional (10-25-50 W, 10 min) or FES assisted (unloaded, 10 min) in a crossover design. Whole body and leg muscle metabolism were assessed by indirect calorimetry with concomitant repeated measurements of femoral venous-arterial differences of blood gases, glucose, lactate and amino acids. RESULTS: Unloaded FES cycling, but not volitional exercise, led to a significant increase in across-leg lactate production (from -1.1±2.1 to 5.5±7.4 mmol/min, p<0.001) and mild elevation of arterial lactate (from 1.8±0.7 to 2.5±0.8 mM). This occurred without widening of across-leg veno-arterial (VA) O2 and CO2 gaps. Femoral SvO2 difference was directly proportional to VA difference of lactate (R2 = 0.60, p = 0.002). Across-leg glucose uptake did not change with either type of exercise. Systemic oxygen consumption increased with FES cycling to similarly to 25W volitional exercise (138±29% resp. 124±23% of baseline). There was a net uptake of branched-chain amino acids and net release of Alanine from skeletal muscle, which were unaltered by either type of exercise. CONCLUSIONS: Unloaded FES cycling, but not volitional exercise causes significant lactate production without hypoxia in skeletal muscle. This phenomenon can be significant in vulnerable patients' groups.
Keywords: Femoral Vein; Young Adult; aminokyseliny; arteria femoralis; Lactic Acid; Male; Oxygen; bérec; nepřímá kalorimetrie; mladý dospělý; elektrická stimulace; Femoral Artery; klinické křížové studie; terapie cvičením; Supine Position; Adult; Muscle, Skeletal; supinační poloha; dospělí; Electric Stimulation; mužské pohlaví; Calorimetry, Indirect; kosterní svaly; cyklistika; spotřeba kyslíku; kyselina mléčná; Oxygen Consumption; lidé; kyslík; Carbon Dioxide; ženské pohlaví; Leg; Humans; Exercise Therapy; Bicycling; oxid uhličitý; zdraví dobrovolníci pro lékařské studie; vena femoralis; Cross-Over Studies; Female; Amino Acids; Healthy Volunteers